Mental Health Literacy: Strengthening Community Mental Health with Awareness - Özlem Şahin Altun; Duygu Özer (Psikiyatride Güncel Yaklaşımlar, 2022)
Due to the increasing mental problems today, protecting and strengthening the mental health of the society has become an even more important issue. The lack of knowledge and stigmatizing attitudes of the societies about mental disorders lead to the inability to treat mental disorders effectively in the early period. In this context, increasing the mental health literacy of the society within the scope of preventive mental health services will be an important step. Mental health literacy is a very new concept for our country, it is not fully known and it is seen that studies on this subject are limited. Therefore, in this review, the concept of mental health literacy, its importance, interventions to improve it and what psychiatric nurses can do about it will be discussed. This review will provide important and up-to-date data to the literature and will raise awareness of mental health professionals about the need for mental health literacy intervention studies.